E-Learning and Development of New Courses and Scientific Work in the Field of Pharmaceutical Technology - Hans Leuenberger; Natalia Menshutina; Gabriele Betz; Maxim N. Puchkov (CHIMIA, 2006)
Since 2001, the Institute of Pharmaceutical Technology (IPT) at the University of Basel and the Mendeleyev University of Chemical Technology of Russia (MUCTR) have established an institutional partnership (IP), which is supported by the Swiss National Science Foundation (SNF) in the framework of the SCOPES (Scientific Cooperation between Eastern Europe and Switzerland) project. The results of this collaboration are the new teaching technologies that were introduced at the MUCTR and the IPT. The former include multimedia lectures in pharmaceutical technology, which are held in parallel at University of Basel and MUCTR, and the educational web-portal 'Pharmacy online', which was awarded a medal at the 4th Moscow International Salon of Innovations. The multimedia lectures are popular with and helpful for MUCTR students, because they can compensate to a certain extent the lack of equipment at the MUCTR. However, multimedia lectures can never replace hands-on training and therefore the continuation of the collaboration is ongoing. In this respect SNF decided in 2005 to give continuous support for this cooperation through the grant entitled 'New Concepts in Training Industrial Pharmacists and Pharmaceutical Engineers to Be Developed and Implemented at the Russian-Swiss Scientific and Education Centre in MUCTR'. This centre was established as a result of the previous grant. The development and implementation of a unique and innovative learning concept on the basis of the Russian-Swiss scientific and educational centre involving the Russian pharmaceutical and biotechnological industry, is an ongoing activity.